Prevalence of Echinococcus granulosus and Taenia hydatigena in caribou in north-central Canada - Thomas, Donald C. (Rangifer, 1996)
There are few data on the prevalence and infection intensity of parasites in large samples of caribou (Rangifer tarandus). Therefore, differences related to sex, age, and season are unknown. The effect of parasites on the health and condition of caribou also is poorly known. From 1980 through 1987, 1258 barren-ground caribou (R.t. groenlandicus) were collected from the Beverly herd in north-central Canada. The prevalence in lungs of cysts of the hydatid tapeworm (Echinococcus granulosus) increased significantly with age of caribou. Prevalence in females was 2% in the 2-5 year class and 8% in older individuals. Cysts were more prevalent in young females compared with young males. Reductions in physical condition and fecundity were not statistically significant. The prevalence of Taenia hydatigena cysts in livers increased significantly with age of host but not with sex and condition of the hosts. The use of parasite prevalence as an index of predation rate is discussed.